Polyethylene and the Nucleating Agent: Dibenzylidene Sorbitol, a Neutron Scattering Study - Mitchell, Geoffrey R. (2019)
Dibenzylidene Sorbitol is a very effective clarification additive for isotactic polypropylene. It is not effective with polyethylene although recent studies have shown that it can act as an effective nucleating and directing agent. We employ small-angle neutron scattering measurements to more fully understand the behavior of dibenzylidene sorbitol in a polyethylene matrix. The small-aangle neutron scattering clearly shows that the disappearance of the DBS fibrils is concentration dependent and for 2% DBS the midpoint of the dissolution is at 145°C and for 1% is ~ 20°C lower.